Phytophagous Features Of Californian And Purple Scale Insects In The Jujube Agrocenosis (Texas Journal of Agriculture and Biological Sciences, 2024)
Ten species of diaspid scale insects were studied in the jujube agrocenosis. The identified species were distributed across the following genera: Diaspidiotus (4 species), Salicicola (1 species), Parlatoria (2 species), and Lepidosaphes (3 species).